2014
DOI: 10.1099/vir.0.059808-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of memory CD4+ T-cells in semi-wild mandrills (Mandrillus sphinx) naturally infected with species-specific simian immunodeficiency virus SIVmnd-1

Abstract: Simian immunodeficiency virus (SIV) infection is found in a number of African primate species and is thought to be generally non-pathogenic. However, studies of wild primates are limited to two species, with SIV infection appearing to have a considerably different outcome in each. Further examination of SIV-infected primates exposed to their natural environment is therefore warranted. We performed a large cross-sectional study of a cohort of semi-wild mandrills with naturally occurring SIV infection, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…These results are in agreement with studies of experimentally infected AGMs, where sCD14 levels remained stable following infection (Pandrea et al, 2006b, 2012a, 2012a, 2007b). A separate study of semi-wild mandrills in Gabon confirmed these results by showing that plasma levels of sCD14 remained unchanged following SIVmnd1-infection (Greenwood et al, 2014). …”
Section: Post-transmission Features That May Impact Siv Pathogenesmentioning
confidence: 74%
See 1 more Smart Citation
“…These results are in agreement with studies of experimentally infected AGMs, where sCD14 levels remained stable following infection (Pandrea et al, 2006b, 2012a, 2012a, 2007b). A separate study of semi-wild mandrills in Gabon confirmed these results by showing that plasma levels of sCD14 remained unchanged following SIVmnd1-infection (Greenwood et al, 2014). …”
Section: Post-transmission Features That May Impact Siv Pathogenesmentioning
confidence: 74%
“…Also, SM CD4 + T CM proliferation levels are lower than in RMs and the RM T CM proliferation correlates with viral replication (McGary et al, 2014). Yet, a recent study of mandrills in Gabon found a significant decrease in memory T-cells populations that was correlated with the duration of infection (Greenwood et al, 2014). However, other studies of the same mandrill cohort did not find similar features (Apetrei et al, 2011).…”
Section: Post-transmission Features That May Impact Siv Pathogenesmentioning
confidence: 99%
“…During this period, one of the hallmark features of nonpathogenic SIV infection is the rapid attenuation of ISG expression to baseline levels in the chronic phase (Bosinger et al 2009;Jacquelin et al 2009;Lederer et al, 2009). Additionally, natural hosts maintain high viral loads, but recover CD4+ T cell homeostasis, though variation in the effects of SIV infection on CD4+ T cell homeostasis have been observed in natural hosts (Keele et al 2009;Greenwood et al, 2014). While the upregulation of ISGs persists in pathogenic SIV/HIV infection in macaques and humans (Paiardini & Müller-Trutwin, 2013), rapid control of ISG expression occurs in natural hosts (AGMs and SMs) within 4-8 weeks post-infection (Bosinger et al 2009;Jacquelin et al 2009).…”
Section: Nonpathogenic Siv Infectionmentioning
confidence: 99%
“…Over 40 species of nonhuman primates are naturally infected with endemic strains of SIV, including African apes and African members of the Old World monkey subfamilies Cercopithecinae and Colobinae (VandeWoude & Apetrei, 2006;Worobey et al, 2010). However, studies on the pathogenicity of SIV infection in natural hosts have been limited to chimpanzees and three species within the Cercopithecinae (African green monkey (AGM), sooty mangabey (SM), and mandrill (MND; Apetrei et al, 2011;Bosinger et al, 2009;Greenwood et al, 2014;Jacquelin et al, 2009;Keele et al, 2009;Ma et al, 2013). Recently, studies in SIVcpz-infected chimpanzees (Keele et al, 2009) and SIVmnd-1-infected MNDs (Greenwood et al, 2014) have demonstrated variation in the pathogenic effects of SIV infection in natural hosts, but to our knowledge no study has assessed the relationship between SIV infection and host gene expression patterns in a wild population of natural SIV hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation